中国乡镇企业技术创新的制约因素及对策分析 = Technological innovation in township enterprises of China : obstacles and strategies - 阎会力 Yan, Huili (2008)
In this thesis, the applications of some new theories on the technological innovation in current township enterprises of China are analyzed. Based on the analysis, the main obstacles to technological innovation at both micro and macro levels are explored. Suggestions are proposed to promote technological innovations in township enterprises.